Bian-stone ironing and rubbing therapy combined with Traditional Chinese Medicine penetration therapy for postoperative constipation in a lung cancer patient undergoing chemotherapy (砭石熨摩中药透入法治疗肺癌患者化疗后便秘1例的护理) - GAO Yaqian (高雅倩); GUO Huanli (郭换利); HUANG Yanping (黄砚萍); FENG Wenying (冯文英); ZHANG Guohong (张国红); ZHANG Xuelian (张雪莲) (中西医结合护理)
This article summarizes the nursing practice of a lung cancer patient with constipation after chemotherapy treated with Bian-stone ironing and rubbing therapy combined with Traditional Chinese Medicine penetration therapy. Through scientific nursing evaluation and syndrome differentiation, the patient's nursing plan was determined. Based on the basic theory of Traditional Chinese Medicine, the Bian-stone ironing and rubbing therapy combined with Traditional Chinese Medicine penetration therapy were used to relieve constipation. At the same time, nursing interventions such as defecation guidance, dietary regulation, exercise, and medication guidance were adopted to further improve clinical symptoms and achieve significant therapeutic effects on constipation. (本文总结1例砭石熨摩中药透入治疗肺癌患者化疗后便秘的护理经验。通过科学的护理评估和辨证分型, 确定患者护理方案, 基于中医基础理论, 采用砭石熨摩中药透入法和手指点穴缓解便秘, 同时配合排便指导、饮食调护、运动锻炼、用药指导等护理干预, 进一步改善患者临床症状, 减轻疼痛。)